Effect of Tamarind Turmeric Drink on Dysmenorrhea in Women of Reproductive Age: Efek Pemberian Minum Kunyit Asam terhadap Dismenore pada Wanita Usia Subur - Rizky, Rizky Putri Amalia; Dinengsih, Sri; Kundaryanti , Rini (Universitas Muhammadiyah Sidoarjo, 2023)
Women of childbearing age experiencing menstruation experience physical discomfort on the eve of or during menstruation including menstrual pain called dysmenorrhea that occurs during menstruation due to uterine muscle spasms. Drug treatments and supplements are commonly used to treat menstrual cramps. Turmeric and tamarind drink is a menstrual cramps treatment that is safe, easy to use and has no side effects. The active ingredients in turmeric function as antioxidants, anti-inflammatory, and pain relievers, while tamarind (tamarind) fruit contains antioxidants, anti-inflammatory drugs, antipyretics, and sedatives. Therefore, drinking tamarind turmeric water can reduce the severity of menstrual cramps. Objective: to determine the effect of giving tamarind turmeric drink on the incidence of dysminorrhea in women of childbearing age at TPMB